2019
DOI: 10.1080/23802359.2019.1640090
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete chloroplast genome of leek Allium porrum L. (Amaryllidaceae)

Abstract: The complete chloroplast genome sequence of Allium porrum was determined by Illumina single-end sequencing. The complete plastid genome was 152,732 bp in length containing a large single copy (LSC) of 81,744 bp and a small single copy (SSC) of 17,910 bp, which were separated by a pair of 26,524 bp inverted repeats (IRs). A total of 133 genes were annotated, including 80 protein-coding genes, 38 tRNA genes, 8 rRNA genes, and 7 pseudogenes. The overall GC contents of the plastid genome were 36.7%. Unlike A. sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…The cemA gene is not essential for photosynthesis, however in high light conditions cemA-lacking mutants of Chlamydomonas reinhardtii showed increased light sensitivity (Rolland et al, 1997). The rps2 gene is functional in Amaryllidoideae and Agapanthus coddii but has pseudogenized due to internal stop codons in Allium, which has been reported previously by Filyushin et al (2019), Omelchenko et al (2019), andXie et al (2019). Kim et al (2015) and Kim et al (2020) showed a correlation between the presence of ndhF and the organisation of the IR-SSC junctions in Orchidaceae, and proposed that the loss of ndhF leads to destabilization of the IR-SSC junctions.…”
Section: Discussionsupporting
confidence: 68%
“…The cemA gene is not essential for photosynthesis, however in high light conditions cemA-lacking mutants of Chlamydomonas reinhardtii showed increased light sensitivity (Rolland et al, 1997). The rps2 gene is functional in Amaryllidoideae and Agapanthus coddii but has pseudogenized due to internal stop codons in Allium, which has been reported previously by Filyushin et al (2019), Omelchenko et al (2019), andXie et al (2019). Kim et al (2015) and Kim et al (2020) showed a correlation between the presence of ndhF and the organisation of the IR-SSC junctions in Orchidaceae, and proposed that the loss of ndhF leads to destabilization of the IR-SSC junctions.…”
Section: Discussionsupporting
confidence: 68%
“…The cemA gene is not essential for photosynthesis, however in high light conditions cemA -lacking mutants of Chlamydomonas reinhardtii showed decreased photosynthetic efficacy ( Rolland et al, 1997 ). The rps2 gene is functional in Amaryllidoideae and Agapanthus coddii but has pseudogenised due to internal stop codons in Allium , which has been reported previously by Filyushin, Beletsky & Kochieva (2019) , Omelchenko et al (2020) and Xie et al (2019) .…”
Section: Discussionsupporting
confidence: 67%
“…Complete plastome sequences were first sequenced and arranged for the most economically important species of Allium : onion, A. cepa ( von Kohn et al, 2013 ), garlic, A. sativum ( Filyushin et al, 2016 ), edible species A. ursinum and A. paradoxum ( Omelchenko et al, 2020 ). Another wide spectrum of wild and cultivated Allium species plastomes were sequenced and partially analyzed ( Filyushin et al, 2018 , 2019 ; Xie et al, 2019 , 2020 ; Liu et al, 2020 ; Namgung et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%